Climate change hazard index reveals combined risks to United States drinking water utilities - Zia J Lyle; Jeanne M VanBriesen; Constantine Samaras (Environmental Research: Climate)
Drinking water utilities are exposed to a range of climate change hazards that can affect their ability to deliver safe drinking water. We use climate change mid-century projections to assess seven hazards for 42 786 utility systems (serving 283 million people) across the contiguous United States and develop a combined climate hazard index that allows for risk comparisons. All utilities are exposed to climate hazards, and around half, serving 178 million people (53% of current population), could experience large changes in one or more climate hazards that could affect an aspect of system reliability, including water resources, infrastructure, or operations. While utilities located in Western regions and coastal areas have higher climate hazard index values, there are utilities serving different population sizes in all geographic regions with elevated climate risk. Few utilities have developed climate adaptation plans and many may have existing vulnerabilities. This index provides multiple stakeholders, including utilities, regulators, and investors, with usable and accessible climate information.